Pengaruh Kualitas Produk, Harga, Lokasi, dan Pelayanan Terhadap Keputusan Pembelian Pada Toko UD. Nayla Jaya di Asam Jawa - Septian, Septian (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The purpose of this study is to determine the effect of product quality, price, location and service on the purchase decision on UD. Nayla Jaya in Asam Java either partially or simultaneously. Data collection using field studies (observation), questionnaire interviews and documentation. Work on data analysis methods using the help of SPSS 26.0 for windows software. This study used a sample of 82 buyers taken by using Accidental Sampling. The results of the study based on the simultaneous Test (Test F) showed that product quality, price, location and service simultaneously significantly affect the purchase decision at UD store. Nayla Jaya in Asam Jawa, where the value of F (28.728) > F (2.49) with the significance of 0.000 < 0.05. The results of partial hypothesis testing (t test) showed that product quality has a positive and significant effect on purchasing decisions at UD stores. Nayla Jaya in Asam jawa, where the value of t (3.111) > t (1.664) with a significance level of 0.003 < 0.05. Price negatively and significantly affect the purchase decision at UD stores. Nayla Jaya in Asam Jawa, with a value of t -2.640 < t ((1.664) with a significance level of 0.010 < 0.05. Location has a positive and significant effect on purchasing decisions at UD stores. Nayla Jaya in Asam Java, with a value of t (2.822) > t ((1.664) with a significance level of 0.006 < 0.05. Partial service has a positive and significant effect on purchasing decisions at UD stores. Nayla Jaya in Asam Java, with a value of t (5.410) > t ((1.664) with a significance level of 0.000 < 0.05.Â  Based on the determination test results obtained Adjusted R Square value of 0.574 means 57.40% of purchasing decisions are explained by product quality, price, location, and service. While the remaining 42.60% can be explained by factors that are not studied in this study, such as promotions, discounts, and so forth.